Angiolymphoid hyperplasia of external ear treated with intralesional radiofrequency ablation. (20th April 2018) - Yadav, Deepika; Singh, Sanjay; Bhari, Neetu; Gupta, Somesh
Abstract : A 21-year-old woman presented with multiple erythematous to skin-coloured dome-shaped firm papules and plaques over the right ear concha and external auditory canal for 1 year. It was associated with occasional itching and bleeding. Her main concern was cosmetic disfigurement. Biopsy showed presence of multiple proliferating blood vessels lined by plump epithelioid endothelial cells surrounded by dense infiltrate of lymphocytes, histiocytes and eosinophils. Other routine investigations were within normal limits. A diagnosis of angiolymphoid hyperplasia with eosinophilia was made. A single sitting of intralesional radiofrequency ablation (Vesalius, coagulation mode; fanning technique) using 18-G intravenous cannula was done. This led to almost complete resolution with no recurrence at 3 months follow-up. There was no evidence of scarring or depigmentation.